2017
DOI: 10.14417/ap.1260
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life in nurses: Contribution for the validation of the Portuguese version of the Professional Quality of Life Scale-5 (ProQOL-5)

Abstract: Job stress and burnout are highly prevalent in healthcare professionals, and nurses in particular. Given its deleterious consequences not only for professionals' well-being but also for patients and organizations, it is important to have adequate measures to assess professional quality of life. This study aimed to offer a contribution for the Portuguese validation of the Professional Quality of Life Scale-5. This scale was designed to measure three dimensions of professional quality of life: compassion satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 38 publications
6
22
1
6
Order By: Relevance
“…However, most studies investigating the relationship between secondary traumatization and burnout have used ProQoL, with a recent meta-analysis reporting an overall average correlation of r = .69 between burnout and secondary traumatization which increased to r =.74 in studies where both constructs were measured using the ProQoL (Cieslak et al, 2014). This finding might lend support to studies that have suggested that items measuring secondary traumatization and burnout are in fact measuring one rather than two factors (Duarte, 2017;Heritage et al, 2018). Conversely, it has been suggested that the high correlation between secondary traumatization and burnout is partially accounted for by the general distress associated with both conditions (Stamm, 2010).…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…However, most studies investigating the relationship between secondary traumatization and burnout have used ProQoL, with a recent meta-analysis reporting an overall average correlation of r = .69 between burnout and secondary traumatization which increased to r =.74 in studies where both constructs were measured using the ProQoL (Cieslak et al, 2014). This finding might lend support to studies that have suggested that items measuring secondary traumatization and burnout are in fact measuring one rather than two factors (Duarte, 2017;Heritage et al, 2018). Conversely, it has been suggested that the high correlation between secondary traumatization and burnout is partially accounted for by the general distress associated with both conditions (Stamm, 2010).…”
mentioning
confidence: 80%
“…The strongest cross-factor loadings were seen for ST7 and ST11. ST11 (feeling 'on edge' about various things) has previously been suggested to measure 'wear and tear' associated with burnout over secondary traumatization (Duarte, 2017), and the content of ST7 (difficulties separating personal life from life as a helper) resembles work-family conflict that has previously been associated with both burnout and secondary traumatization in child-protection workers (Baugerud, Vangbaek, & Melinder, 2018). Hence, these items appear to be measuring experiences that are associated with both burnout and secondary traumatization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A consistência interna para essa amostra foi .854 para satisfação por compaixão, .762 para fadiga por compaixão e .626 para burnout. Em outros estudos em que se utilizou a versão em português dessa escala, as estimações de consistência interna foram .88 para satisfação de compaixão, .82 para fadiga por compaixão e .86 para burnout (Duarte, 2017).…”
Section: Escala Deunclassified